Strategic Management of Intolerance Mitigation Through Inclusive Islamic Education from the Perspective of the Qur'an - Hasan Basri (Riwayat: Educational Journal of History and Humanities, 2025)
The study discusses the strategic role of intolerance mitigation management through inclusive Islamic education with the perspective of the Qur'an. This study was conducted through library research, namely by critically reading the books of 'ulmul Qur'n on intolerance and inclusive education. The results of the study are that inclusive Islamic education from the perspective of the Qur'an is able to overcome or mitigate intolerant behavior, because intolerant behavior that includes attitudes and actions that do not want to accept differences has a significant negative impact on the world of education and the community environment. As a place where diverse ideas, cultures, and values gather, education becomes the foundation for tolerance and deep understanding, with this inclusive Islamic education can make every individual or group able to accept and appreciate every difference, live side by side peacefully and calmly, so that a peaceful and prosperous society, country and nation are formed. In the view of the Qur'an there are several ways in efforts to mitigate intolerance through inclusive Islamic education, including ten methods, namely; 1) recognizing, 2) analytical and synthetic thinking, 3) group and instructional 4), practice and situational, 5) guidance and counseling, 6) questions and answers and discussions, 7) tarhb and targhb, 8) stories and examples, 9) repentance and amtsl, 10) habituation. From these methods, it is formulated with verses of the Qur'an and interpretations as evidence that inclusive Islamic education is in line with Islamic teachings in regulating the order of human life on this earth, especially in the context of education, until the creation of a peaceful life that respects differences between individuals and groups.